Miniature atomic scalar magnetometer for space based on the rubidium isotope 87Rb. Issue 8 (3rd August 2016) - Korth, Haje; Strohbehn, Kim; Tejada, Francisco; Andreou, Andreas G.; Kitching, John; Knappe, Svenja; Lehtonen, S. John; London, Shaughn M.; Kafel, Matiwos
Abstract: A miniature atomic scalar magnetometer based on the rubidium isotope 87 Rb was developed for operation in space. The instrument design implements both Mx and Mz mode operation and leverages a novel microelectromechanical system (MEMS) fabricated vapor cell and a custom silicon‐on‐sapphire (SOS) complementary metal‐oxide‐semiconductor (CMOS) integrated circuit. The vapor cell has a volume of only 1 mm 3 so that it can be efficiently heated to its operating temperature by a specially designed, low‐magnetic‐field‐generating resistive heater implemented in multiple metal layers of the transparent sapphire substrate of the SOS‐CMOS chips. The SOS‐CMOS chip also hosts the Helmholtz coil and associated circuitry to stimulate the magnetically sensitive atomic resonance and temperature sensors. The prototype instrument has a total mass of fewer than 500 g and uses less than 1 W of power, while maintaining a sensitivity of 15 pT/√Hz at 1 Hz, comparable to present state‐of‐the‐art absolute magnetometers. Key Points: Atomic magnetometer for space has a total mass of less than 500 g and uses less than 1 W of power Miniaturization enabled by MEMS fabrication techniques and low‐power semiconductor lasers Sensitivity of 15 pT/√Hz at 1 Hz is comparable to present state‐of‐the‐art atomic magnetometers